2013
DOI: 10.1189/jlb.0911449
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-induced CCN2 expression in human lung fibroblasts requires the c-Src/JAK2/STAT3 pathway

Abstract: Thrombin is a multifunctional serine protease and an important fibrotic mediator that induces CCN2 expression. We previously showed that thrombin induces CCN2 expression via an ASK1-dependent JNK/AP-1 pathway in human lung fibroblasts. In this study, we further investigated the roles of c-Src, JAK2, and STAT3 in thrombin-induced CCN2 expression. Thrombin-induced CCN2 expression and CCN2-Luc activity were attenuated by a JAK inhibitor (AG490) and JAK2DN, STAT3DN, and the STAT decoy ODN. Moreover, transfection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…Tao et al have also demonstrated that there is an increase of JAK1 and STAT1 activity after CTGF stimulation of the human hypertrophic scar fibroblasts . In human lung fibroblasts, CCN2 expression is induced by JAK2's activation of STAT3 after JAK2 is activated by thrombin through its effect on c‐Src . The earlier studies all accord with what we have obtained in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Tao et al have also demonstrated that there is an increase of JAK1 and STAT1 activity after CTGF stimulation of the human hypertrophic scar fibroblasts . In human lung fibroblasts, CCN2 expression is induced by JAK2's activation of STAT3 after JAK2 is activated by thrombin through its effect on c‐Src . The earlier studies all accord with what we have obtained in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Growth factors, cytokines and hormones are classical regulators of CCN2, which include transforming growth factor (TGF)-β, bone morphogenetic protein (BMP)-2, angiotensin II, glucocorticoids, monocyte chemotactic protein (MCP)-1 and interferon (IFN)-γ [9][10][11]. Other extracellular signalling molecules, such as haemodynamic endothelin (ET)-1, secreted frizzled-like protein (sFRP)-2, anti-proliferative factor and thrombins are also reported to up-regulate CCN2 production [11,14,15]. In this point of view, one should note that induced CCN2 directly interacts with TGF-β molecules, which modulates its signalling [5].…”
Section: Gene Structure and Regulationmentioning
confidence: 99%
“…2D and E), indicating c-Src as the major downstream molecule of FAK. c-Src could activate STAT3 directly or indirectly through JAK2 (22,23). We demonstrated that CAFs had concomitantly elevated levels of p-c-Src, p-JAK2 and p-STAT3, which were markedly decreased in FAP À CAFs or FAK inhibitortreated CAFs (Fig.…”
Section: Fap Induces Inflammatory Fibroblasts By Activating Stat3 Thrmentioning
confidence: 77%